Analisis Kemajuan Tambang Terhadap Perancangan Mine Plan pada Aktivitas Overburden Removal - Aftri Sa Putra; Hepryandi L. D. J Usup; Noveriady (Jurnal Riset Teknik Pertambangan, 2023)
Abstract. Mining progress is the changes that occur in the mining area after mining activities have been carried out. In this case, it is a change in surface shape due to the mining process. This change in shape is measured using a measuring instrument total station. Mining progress occurs because of activity overburden removal namely the process of moving overburden from the mining front to disposal. Activity overburden removal at PT. Rimau Tangguh Perkasa has 2 units of loading digging equipment to carry out work with 2 units fleet each unit has an appropriate capacity for the transportation equipment. The progress of the mine has the aim of knowing the transition design pit every time activities are carried out in the mining area from the results overburden removal based on changes that occur in the mining area. PT. Rimau Tangguh Perkasa has mine progress with good excavation results overcut, undercut, over-stripping and in plan to planning mine plan in May, June and July 2023. On results overlay mine plan design regarding mining progress in May 2023 has results overcut 16.008,98 BCM, undercut 41.904 BCM, over-stripping 68,989 BCM and progress in plan 80,148 BCM. In June 2023 have results overcut 24.215,31 BCM, undercut 66.499 BCM, over-stripping 23,248 BCM and progress in plan 133,321 BCM. And in July 2023 have results overcut 22.369 BCM, undercut 66.499 BCM, over-stripping 12,789 BCM and progress in plan 173.605 BCM. Abstrak. Kemajuan tambang adalah perubahan-perubahan yang terjadi pada daerah tambang setelah dilakukan kegiatan penambangan. Dalam hal ini adalah perubahan bentuk permukaan karena proses penambangan. Perubahan bentuk ini diukur menggunakan alat ukur total station. Kemajuan tambang terjadi karena adanya aktivitas overburden removal yaitu proses pemindahan tanah penutup dari front penambangan menuju disposal. Kegiatan overburden removal di PT. Rimau Tangguh Perkasa memiliki 2 unit alat gali muat untuk melakukan pekerjaan dengan 2 fleet masing-masing unit memiliki kapasitas yang sesuai terhadap alat angkut. Kemajuan tambang memiliki tujuan untuk mengetahui peralihan design pit penambangan dari hasil overburden removal berdasarkan perubahan-perubahan yang terjadi pada daerah tambang. PT. Rimau Tangguh Perkasa memiliki kemajuan tambang dengan hasil penggalian yang overcut, undercut, over-stripping dan in plan terhadap perancangan mine plan pada bulan Mei, Juni dan Juli 2023. Pada hasil overlay mine plan design terhadap kemajuan tambang bulan Mei 2023 memiliki hasil overcut 16.008,98 BCM, undercut 41.904 BCM, over-stripping 68.989 BCM dan progress in plan 80.148 BCM. Pada bulan Juni 2023 memiliki hasil overcut 24.215,31 BCM, undercut 66.499 BCM, over-stripping 23.248 BCM dan progress in plan 133.321 BCM. Dan pada bulan Juli 2023 memiliki hasil overcut 22.369 BCM, undercut 66.499 BCM, over-stripping 12.789 BCM dan progress in plan 173.605 BCM.